Structural Unemployment in Luxembourg : Bad Luck or Rational Choice? - Gbohoui, William (IMF Working Papers; Working Paper ;, 2019)
This paper combines both micro and macro approaches to identify the drivers of (un)employment and inactivity in Luxembourg. The young, low-skilled, and non-EU migrants are found to be the most vulnerable groups in the labor market. In addition to skills mismatches, work disincentives embedded in the tax-benefit system constitute a factor explaining structural unemployment. High unemployment of young and low-skilled workers reflects substantial unemployment traps, while disincentives for second earners (respectively the generosity of the pension system) contribute to lower labor market participation of women (respectively seniors). Further reduction of structural unemployment requires better integration of vulnerable groups into the labor market and improved targeting of benefits to make work more rewarding.